Synchronized Tactile Stimulation on Upper Limbs Using a Wearable Robot for Gait Assistance in Patients With Parkinson's Disease - Kishi, Takayuki; Ogata, Taiki; Ora, Hiroki; Shigeyama, Ryo; Nakayama, Masayuki; Seki, Masatoshi; Orimo, Satoshi; Miyake, Yoshihiro (Frontiers in Robotics and AI, 2020)
This study aimed to investigate whether using a wearable robot applying interactive rhythmic stimulation on the upper limbs of patients with Parkinson’s disease (PD) could affect their gait. The wearable robot presented tactile stimuli on the patients’ upper limbs, which was mutually synchronized with the swing of their upper limbs. We conducted an evaluation experiment with PD patients (n = 30, Modified Hoehn-Yahr = 1–3), in which they were instructed to walk 30 m under four different conditions: 1) not wearing the robot before the intervention, 2) wearing the robot without the rhythm assistance, 3) wearing the robot with rhythm assistance, and 4) not wearing the robot after the intervention. The arm swing width, normalized stride length, and normalized velocity were larger when the robot assisted the rhythm of the patients’ gait than when the patients wore the robot without the assistance. The stride duration CV was smaller when the robot assisted the patient’s rhythm than when the participants wore the robot without assistance. These results revealed the gait-assistance effect of the robot on PD patients. In addition, the normalized stride length and normalized velocity were larger and the stride duration CV was smaller after the intervention than before the intervention. These results show the immediate after-effect of using the robot intervention. These findings suggest that the interactive rhythmic stimulation on the upper limbs could influence the gait of patients with PD and that the robot may assist with gait rehabilitation for these patients.